2014
DOI: 10.1155/2014/178436
|View full text |Cite
|
Sign up to set email alerts
|

ECG Beats Classification Using Mixture of Features

Abstract: Classification of electrocardiogram (ECG) signals plays an important role in clinical diagnosis of heart disease. This paper proposes the design of an efficient system for classification of the normal beat (N), ventricular ectopic beat (V), supraventricular ectopic beat (S), fusion beat (F), and unknown beat (Q) using a mixture of features. In this paper, two different feature extraction methods are proposed for classification of ECG beats: (i) S-transform based features along with temporal features and (ii) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 20 publications
(33 reference statements)
0
38
0
Order By: Relevance
“…Using MLPNN, ECG signals are recognized and classified more accurately [3,8,9,12,28]. Accuracy of MLPNN increases with number of hidden neurons [25,40]. MLPNN performs static mapping, there are no internal dynamics.…”
Section: Classification Of Ecg Using Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Using MLPNN, ECG signals are recognized and classified more accurately [3,8,9,12,28]. Accuracy of MLPNN increases with number of hidden neurons [25,40]. MLPNN performs static mapping, there are no internal dynamics.…”
Section: Classification Of Ecg Using Neural Networkmentioning
confidence: 99%
“…70% beats for training, 30% beats for testing B RBBB, LBBB, APC, PVC, Paced, APB, Ventricular flutter wave, Fusion of ventricular and normal, Blocked AP beat, Nodal escape beat, Fusion of paced and normal, Ventricular escape beat, Nodal premature beat, Atrial escape, Unclassified.Total 1252 beats for training Normal, LBBB, RBBB, Negative: Ventricular ectopic beats, PVC, Fusion of ventricular and normal. 150 beats from first 5 min for training and other 25 min 60, 30), LBBB(28,14), PVC (45, 25), Atrial fibrillation(30,25), Ventricular fibrillation(28,21), Complete heart block-CHB(28,21), Ischaemic cardiomyopathy(30,18), Sick sinus syndrome(28,14), LBBB (60, 30), PVC (45, 25), Atrial fibrillation(30,20), Ventricular fibrillation(28,21), CHB(28,21), Ischaemic cardiomyopathy(30,18), Sick sinus syndrome (Abnormal: RBBB, LBBB, Paced, PVC, Life threatening: Sick sinus syndrome, Ischemic heart diseases, Ventricular vibrillation beat. 600 beats for training and 400 beats for testing S V. ANALYSIS OF THE SURVEY…”
mentioning
confidence: 99%
“…In this work, the raw ECG signals are decomposed into approximation and detail sub bands up to level 9 using Daubechies ("db6") wavelet basis function [29]. The detail coefficients contain most of the noise information.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…5,6,[9][10][11][12][13][14][15][16]21,[24][25][26] Parameters such as accuracy, sensitivity, and specificity are used in the literature for evaluating the performance of a classifier. Most of the research works reported more than 90% average accuracy, average sensitivity, and average specificity taken over all 5 classes.…”
Section: Introductionmentioning
confidence: 99%